A climate Encouraging the Growth and Flourishing of Monkeypox in Indonesia - Ramadhan Tosepu; Devi Savitri Effendy; Nasaruddin Nasaruddin; Asriati Asriati; Sartiah Yusran (Journal of Public Health and Pharmacy)
Introduction: Introduction: Climate change has significant impacts on human health and has the potential to trigger the emergence of various diseases by changing temperature, rainfall, wind patterns, and sunlight exposure. These changes create environmental conditions that support the survival, reproduction, and spread of disease-causing agents, such as viruses and bacteria. Adaptation of disease agents to these changes increases the risk of disease spreading in the community. In addition, climate change also expands the range of some disease agents, which were previously limited to certain areas, thus having a wider impact. Low temperatures (10–25°C), high humidity (?70%), and limited sunlight (UV index <6) promote the environmental persistence of the monkeypox virus, whereas high temperatures (>30°C) and UV exposure (290–320 nm) accelerate its degradation, influencing transmission patterns and infection risk in humans and animals.